THE USE OF COMMUNICATIVE TEACHER TALK STRATEGY FOR ENGLISH TEACHER OF ELEMENTARY SCHOOL IN THE ERA OF AEC AND GLOBALIZATION - Rustantya, Anggie Intan (English Department of Faculty of Tarbiyah and Teachers Training, 2016)
In this coming globalization and AEC era, the need for global communication and interaction put English into an important part of the peopleâs life. This is due to the fact that English has been widely used as a means of communication in several sectors and levels. Â Being aware of the emergence of AEC and globalization era, the Indonesian government has made efforts to prepare the Indonesian to face the demand of globalization, for example: including English lesson for elementary until tertiary level of education. Teacher has important role in the teaching learning process. Communicative teacher talk used by English teacher of elementary level is hoped to motivate and minimize the students fear in interacting with the teacher during teaching learning process. The researcher conducted this study to an English teacher was able to apply four characteristics of communication teacher talk in primary education. The method use descriptive case study to investigate teacherâs phenomena about English used that she has employed communicative teacher talk. The aim of the research is hoped that there will be the ways to communication in English class of elementary school so the teacher can control and not dominate then, the students can improve their English learning.